The influence of previous preterm birth with singleton pregnancy on the risk of recurrence in subsequent twin pregnancy: a meta-analysis - Pinghua Shen; Wenjun Wu; Yehui Jiang (Journal of Obstetrics and Gynaecology)
Background Preterm birth is a significant obstetrical concern around the globe. With this study, we aimed to determine whether a prior singleton pregnancy preterm birth increases the likelihood of preterm birth in subsequent twin pregnancies. We designed his systematic review to provide valuable information for pregnant women and obstetricians during counselling and for individuals involved in the planning of preventive strategies.Methods We comprehensively searched the PubMed, Embase and Scopus databases to identify relevant studies published until October 2023 following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We applied a random-effects meta-analysis to the data gathered from the selected studies.Results Among the 460 initially identified studies, only eight met the eligibility criteria. The analysis of incidence revealed an event rate of 9.5% (95% CI, 4.4–19.5%) for a history of preterm singleton birth in the cohort of women with subsequent twin pregnancies. Subgroup analyses focused on the risk of preterm twin births (<37 weeks, <34 weeks and <32 weeks) in women with prior preterm singleton births. Our results revealed a significantly elevated risk of subsequent preterm twin births associated with prior preterm singleton births at <37 weeks (OR, 2.94; 95% CI, 1.99–4.33; p < .001), <34 weeks (OR, 1.89; 95% CI, 1.67–2.14; p < .001) and <32 weeks (OR, 2.51; 95% CI, 1.58–3.99; p < .001), without heterogeneity in the included studies.Conclusions Our systematic analysis indicates a consistent and statistically significant association between a history of preterm singleton births and preterm twin births at various gestational ages. These findings underscore the importance of the obstetric history during assessments to predict the risk of preterm births in twin pregnancies. Clinicians should monitor pregnancies with a history of preterm singleton births, as targeted interventions and improved prenatal care can mitigate the risk of preterm birth during twin pregnancies.